Model Akselerasi Pengembangan Sambi Sebagai Desa Wisata Di Yogyakarta Melalui Rintisan Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri Bidang Pariwisata - Angela Ariani (Media Wisata, 2017)
Accelerated Development in tourism of Sambi as a tourism village has already done by applying the concept of community participation. Both in giving an important role to the community as the main actor and empowering them in the tourism developmental activities as well. The aspect of sustainability is also an important one. The researcher finds a new model of accelerated development in tourism on Community-Based Tourism development. From the visual observation and in-depth interview with Mr Haryono as the manager of Sambi tourism village, Mr Sutarjo as the community working group coordinator and Mr Hariman Yudo Raharjo as the chairman of Tourism and Culture Office of Sleman Regency, this research comes to applicative tourism accelerated development model on Community-Based Tourism development at Sambi as tourism village which is the applicable one.